Ketogenic diet in pediatric patients with epilepsy - Bartłomiej Pawlicki; Zofia Maria Misztal; Mateusz Pawlicki; Anna Łopuszyńska; Magdalena Kozioł; Karol Lorenc; Damian Bator (Kazimierz Wielki University, 2019)
Ketogenic diet (KD) is a version of low-carbohydrate diet, that is rich in fat, but also contains enough protein and very low carbohydrates supply. This diet may be one of the treatment option for children with refractory epilepsy and studies show that it reduces seizures. KD may affect behavioural and cognitive functioning in children and adolescents with refractory epilepsy. The main weakness of KD are possible adverse side effects included drowsiness, constipation, weight loss, vomiting, gastroesophageal reflux, fever, hyperlipidaemia and elevated risk of kidney stones development.